2018
DOI: 10.1088/1538-3873/aa9fe5
|View full text |Cite
|
Sign up to set email alerts
|

An H-band Vector Vortex Coronagraph for the Subaru Coronagraphic Extreme Adaptive Optics System

Abstract: The vector vortex is a coronagraphic imaging mode of the recently commissioned Subaru Coronagraphic Extreme Adaptive Optics (SCExAO) platform on the 8 m Subaru Telescope. This multi-purpose high-contrast visible and near-infrared (R-to K-band) instrument is not only intended to serve as a VLT-class "planet-imager" instrument in the northern hemisphere, but also to operate as a technology demonstration testbed ahead of the ELTs-era, with a particular emphasis on small inner-working angle (IWA) coronagraphic cap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
(122 reference statements)
1
23
0
Order By: Relevance
“…75, the planet-tostar contrasts for the SCExAO/CHARIS broadband data in Currie et al (2018) are about a factor of 2-5 better than those reported here for SCExAO/HiCIAO at H band due to the CHARIS data's better PSF quality and utilization of ADI+SDI for PSF subtraction. Similarly, the SCExAO/HiCIAO H-band contrasts in Kühn et al (2018), which were taken on a different date: 2016 November 12 UT, are typically a factor of 2 deeper, likely due to usage of the vector vortex coronagraph.…”
Section: Data Reductionmentioning
confidence: 99%
“…75, the planet-tostar contrasts for the SCExAO/CHARIS broadband data in Currie et al (2018) are about a factor of 2-5 better than those reported here for SCExAO/HiCIAO at H band due to the CHARIS data's better PSF quality and utilization of ADI+SDI for PSF subtraction. Similarly, the SCExAO/HiCIAO H-band contrasts in Kühn et al (2018), which were taken on a different date: 2016 November 12 UT, are typically a factor of 2 deeper, likely due to usage of the vector vortex coronagraph.…”
Section: Data Reductionmentioning
confidence: 99%
“…Second, the SLM-induced phase shift is highly chromatic, as it relies on a scalar phase delay instead of a geometric phase shift like, e.g., the vector vortex 24 or vAPP 25 coronagraphs. One can estimate the related theoretical chromatic coronagraphic null depth leakage from Riaud et al 2003 26 as about 2·10 -3 for 10% bandwidth at H-band: this is a rather serious limiting effect, albeit still negligible by roughly an order of magnitude as compared to routinely achieved on-sky null depths with more achromatic coronagraphs, 6 where wavefront control errors are still dominating the leakage budget. However, as ground-based AO performance and loworder NCPAs (especially tip/tilt jitter control) correction progress in future instruments, one can expect this limitation to detrimentally kick in and set a hard contrast limit, and even more immediately so for space-applications or broadband implementations (as typically required for an integral field spectrograph unit).…”
Section: Spatial-light Modulators (Slm) As Focal-plane Phase Coronagrmentioning
confidence: 86%
“…This level of null depth is still very modest, but we note that it is still very rarely achieved on-sky, even with latest extreme AO instruments. 6 Further custom optimization steps to mitigate the parasitic reflection at the glass-LC interface would involve operating with a thicker high-retardance SLM panel, where the relative change of refractive index of the LC material is smaller, hence possibly opening the door to designing some kind of A/R coating for this optical interface. Even more so, we note that the manufacturer quotes a phase flicker standard deviation of ~ 0.2 rad for our PLUTO-014 panel, which theoretically could limit the null depth to ~ 1.2·10 -2 , 26 while higher retardance panels typically exhibiting phase flicker specifications nearly ten times lower.…”
Section: Lcos-slms As Fpm Coronagraphs For Hci: Performance Limitatiomentioning
confidence: 99%
See 1 more Smart Citation
“…However, in practice this limitation needs to be evaluated, as the contrast penalty for, e.g., a support spider being not masked in the Lyot pupil-plane, is usually quite modest as compared to wavefront control aspects. 33 Another solution compatible with field rotation and ADI -and which could also address the case of higher multiple systems (triples, etc.) -would be to rely on some kind of adaptive focal-plane coronagraphs, which would null several stars in the field-of-view and "follow" their rotation while observing.…”
Section: Discussionmentioning
confidence: 99%